2022
DOI: 10.1111/1475-6765.12515
|View full text |Cite
|
Sign up to set email alerts
|

The pandemic and the question of national belonging: Exposure to covid‐19 threat and conceptions of nationhood

Abstract: Drawing on the behavioural immune system hypothesis, we argue that the prevalence of the Covid‐19 pandemic threat in an individual's respective environment relates to exclusive, ethnic conceptions of nationhood. Referring to the affective intelligence theory, we maintain that specific negative emotions are prompted by the perception of being exposed to a pandemic threat, and these emotional states in turn structure political preferences regarding national belonging. Using an original survey in six European cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 84 publications
(172 reference statements)
1
5
0
Order By: Relevance
“… 1. This article was written as part of the research project ‘The Politics of Public Health Threat’ that is financially supported by the Swiss National Science Foundation (SNSF) and the Berne University Research Foundation. In this context, reference should also be made to the contributions by Freitag and Hofstetter (2022) and Wamsler et al (2022), who are elaborating theoretically and empirically similar designs in a coherent research program.…”
mentioning
confidence: 99%
“… 1. This article was written as part of the research project ‘The Politics of Public Health Threat’ that is financially supported by the Swiss National Science Foundation (SNSF) and the Berne University Research Foundation. In this context, reference should also be made to the contributions by Freitag and Hofstetter (2022) and Wamsler et al (2022), who are elaborating theoretically and empirically similar designs in a coherent research program.…”
mentioning
confidence: 99%
“…For example, the pathogen prevalence theory states that the threat of pathogen exposure can lead to behavioural manifestations of collectivism (Fincher et al, 2008). In line with this, levels of ingroup attraction (Meleady et al, 2021) and national belonging were consistently found to be elevated during the first COVID-19 related lockdown in European countries (Wamsler et al, 2022).…”
Section: Dimensions Of Social Cohesionmentioning
confidence: 89%
“…8 Given that recent research argues that ethnic and civic conceptions of nationhood are understood best not as two distinct concepts but as ideal points within a common sphere, where individuals may subscribe to different indicators to a varying extent (Kunovich, 2009; see also Ariely, 2020; Brubaker, 1999; Reeskens & Hooghe, 2010; Smith, 1991), the operationalisation was conducted in the following way: First, the items on political institutions and language that reflect more civic conceptions of nationhood were reversed to highlight differences between the two sets of items. Second, all four items were combined into one continuous, additive index so that higher values represent a primarily ethnic view on national belonging, whereas lower values show ones that are closer to the civic ideal type (see also McLaren, 2017; Miller & Ali, 2014; Wamsler et al, 2022). 9 To assess if any of the hypothesised relationships is contingent on this particular measurement approach, I employ two further measurements for conceptions of nationhood as a robustness check.…”
Section: Methodsmentioning
confidence: 99%
“…Although originally developed as a two‐dimensional framework at the level of entire nations (Brubaker, 1992; Kohn, 1944), research on individual‐level conceptions of nationhood has long stated that both ideal types exist only in theory (Brubaker, 1999; Kuzio, 2002). Most individuals combine elements of civic and ethnic criteria for defining national belonging (Miller & Ali, 2014; Parekh, 1999; Reeskens & Hooghe, 2010; Sarrasin et al, 2020; Wamsler et al, 2022) and may thus be located at an identifiable point on a sphere between the two ideal types.…”
Section: Theoretical Argumentmentioning
confidence: 99%